(untitled) (Journal of Engineering, 2022)
One of the artificial lightweight aggregates with a wide range of applications is Lightweight Expanded Clay Aggregate. Clay is utilized in the production of light aggregates. Using leftover clay from significant infrastructure development projects to manufacture lightweight aggregates has a favorable environmental impact. This research examines the expanded clay aggregate production process and the impact of processing parameters on its physical and mechanical qualities. It also looks at secondary components that can be used to improve the qualities of concrete with expanded clay aggregates. The effect of the quantity of expanded clay aggregate on the fresh, hardened, and durability qualities of concrete is also studied. Expanded clay aggregates improve workability, fire resistance, sound insulation, and thermal insulation in concrete. Its inclusion, on the other hand, diminishes concrete’s density, strength, elastic modulus, and resistance to freeze-thaw action.